Mulher e sociedade: de corpo dominado a corpo dominante em contos de Lygia Fagundes Telles - Martins, Maria Sárvia da Silva (2015)
Woman, as the society – adopting as reference the Western world – has been facing transformations for a long time. It is exactly the discussion about the directions taken by the relation woman and society along years of History that this work focuses on. Defined as a literary production that reveals a profusion of female profiles, fiction written by Lygia Fagundes Telles presents, in many of its characters, the reality experienced by a group of women. Considering not only History of the Western world, but also the consequences of changes in women’s social position, in the other words, the existence of women’s History, in this dissertation, we seek to demonstrate how the writer designs female representatives who show us some courses of women’s trajectory. To examine the constructions of female identities within the literary discourse – bearing in mind the concept of social gender and the Feminist Literary Theory and Cristicism – is the main reading key of the short stories “A Confissão de Leontina”, “O Espartilho”, “Venha Ver o Pôr do Sol” e “Eu Era Mudo e Só”, objects of analysis in this research. To develop this work we appealed to the studies accomplished by Paul Ricoeur (2010), Pierre Bourdieu (2009), Lúcia Osana Zolin (2009), Elódia Xavier (1994, 2007), among other theorists. With the contributions of these studies and from the perspective of a woman liberation movement, we observe how the sign of domination manifests in literary discourse. For this, we consider the writer’s creation process and reflect about Lygia’s characters constitution as social constructs affected by ideologies, power relations, at last, a set of circumstances to which each epoch is exposed to. As a result we hope to evidence the dialog between Literature and History.